Transformasi Konsep dan Nilai Sedekah dalam Dinamika Ekonomi Islam Kontemporer - In'am Salsabila (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This article analyzes the conceptual transformation and implementation of sadaqah (charity) values within the contemporary Islamic economic context. Sadaqah, traditionally understood as a voluntary charitable act, is undergoing a shift in meaning and role. This research employs a qualitative-descriptive approach using literature review to identify how sadaqah moves from an individual philanthropic practice to a professionalized and institutionalized Islamic philanthropy instrument (ZISWAF). This transformation includes the expansion of the objects of sadaqah (from cash to productive assets and digital charity) and a change in orientation (from consumptive to productive and economic empowerment). The results indicate that contemporary sadaqah plays a significant role as social and financial capital in promoting inclusive economic growth and reducing inequality, aligned with the objectives of maqashid shariah. The implication of this finding is the importance of developing adaptive regulation and governance to maximize the potential of sadaqah within the Islamic social finance ecosystem.